PERAN PEMANGKU KEPENTINGAN DALAM PELAKSANAAN MODEL DESA KONSERVASI DI TAMAN NASIONAL GUNUNG RINJANI - Andi Chairil Ichsan; Rinekso Soekmadi; Soeryo Adiwibowo; Cecep Kusmana (Jurnal Analisis Kebijakan Kehutanan, 2017)
Development of Conservation Village Model (CVM) was expected to enhance the empowerment of communities around the protected area at the Mount Rinjani National Park (MRNP). However, in practice the program did not work optimally. Report on CVM program at MRNP illustrated that the collaboration of CVM management was failed to reach the objective of the program. The objective from this study was to provide an overview regarding the implementation of CVM collaboration at MRNP. This study focused on two villages, Pesanggrahan village and Santong village. The study was carried out from May to July 2016, Data collections were using purposive sampling technique, then analyzed descriptively on the interests and influences of each actor as well as their views on the implementation of CVM. The results showed that the collaborative process undertaken in the development of CVM did not work optimally. MRNP Management Office acted as the central actor in the implementation of CVM,both from the planning to the implementation of the program in the field. Thus, it is necessary to develop a greater collaboration processes which are clear, structured and accountable in encourage the involvement of stakeholders to optimize the implementation of CVM in MRNP.